2020
DOI: 10.20289/zfdergi.609079
|View full text |Cite
|
Sign up to set email alerts
|

Edirne Ekolojik Koşullarında Mavi Taş Yoncası (Melilotus caeruleus (L.) Desr.)’nın Farklı Gelişme Dönemlerindeki Yem Verimi ve Kalitesinin Belirlenmesi

Abstract: caeruleus (L.) Desr.)'nın Farklı Gelişme Dönemlerindeki Yem Verimi ve Kalitesinin Belirlenmesi* Determination of Forage Yield and Quality of Blue Melilot (Melilotus caeruleus (L.) Desr.) at Different Growth Stages under Edirne Ecological Conditions *Bu makale, yüksek lisans tezinden özetlenmiştir. ÖZAmaç: Bu çalışma, farklı gelişme dönemlerinin mavi taş yoncasının ot verimi ve kalitesine etkisinin belirlenmesi amacıyla yapılmıştır. Materyal ve Metot:Edirne ili Hasanağa köyü çiftçi koşullarında 2016-2018 yıllar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Previous researchers determined that the yellow sweet clover herbage at the flowering stage included about 7% ash, 38-43% NDF and 22-33% ADF in DM (Canbolat and Karaman 2009;Çaçan et al, 2015). In another study, Ateş and Seren (2020) demonstrated that the CP content of Melilotus caeruleus herbage was decreased by the growth stage, and ADF and NDF contents were increased by the growth stage. The CP content of yellow sweet clover was correlated with ADFom and NDFom contens.…”
Section: Discussionmentioning
confidence: 95%
“…Previous researchers determined that the yellow sweet clover herbage at the flowering stage included about 7% ash, 38-43% NDF and 22-33% ADF in DM (Canbolat and Karaman 2009;Çaçan et al, 2015). In another study, Ateş and Seren (2020) demonstrated that the CP content of Melilotus caeruleus herbage was decreased by the growth stage, and ADF and NDF contents were increased by the growth stage. The CP content of yellow sweet clover was correlated with ADFom and NDFom contens.…”
Section: Discussionmentioning
confidence: 95%